The Situation of E-Learning at Higher Education in Vietnam in the 4th Industrial Revolution Age - Hoa, Nguyen Thi Kim; Nga, Pham Thanh (Advances in Social Sciences Research Journal, 2026)
E-learning has changed strongly the process of self-learning due to the ability to personalize as well as satisfy demand of learners. E-learning has applied at many universities today, in the 4th industrial revolution era. Many application software has been used to replace human beings in imparting knowledge, testing and evaluating the quality of training. In this paper, the authors present some analysis and evaluation of the current online teaching and learning methods and recommend solutions to enhance the interaction and active in the teaching and learning process to improve the quality of online education in Vietnam for the next period.